STUDYING CLOUD COMPUTING TECHNOLOGY COMPARATIVELY - Muhammad Ahmad Baballe; Abdulrahman Yusuf Abdullahi; Mukhtar Ibrahim Bello; Sadiku Aminu Sani; Amina Ibraim (IPHO-Journal of Advance Research in Science And Engineering, 2024)
In order to provide quicker innovation, adaptable resources,and scale economies, cloud computing is the supply of computing services, including servers, storage, databases, networking, software, analytics, and intelligence, over the Internet. As technology advanced in recent years, cloud technologies were increasingly utilized. Cloud technologies are appealing because data may be stored, transmitted to numerous locations at once, and accessed at any time. It is a system that enables data storage on the Internet, releasing users from the constraints of physical settings and storage devices and enabling access from any location at any time.